Development of Inkuiri Model Learning Tools Guided to Improve Concept Mastery Learner Physics - Yuliati Yuliati; Aris Doyan; Haerunnisyah Sahidu (Postgraduate, University of Mataram, 2021)
This study aims to determine the validity, practicality, and effectiveness of guided inquiry learning models to improve students' mastery of physics concepts. This type of research includes research and development of Research and Development (RnD) with the research design used is the 4D model which consists of define, design, develop and disseminate. Products developed in the form of a syllabus, lesson plans, student worksheets, test instruments in the form of questions, and learning videos. The product validity was analyzed by determining the value of the content validator index (CVI) through a questionnaire. Practicality is obtained from student response questionnaires and learning implementation sheets. Furthermore, the effectiveness is obtained from a limited trial to obtain the N-gain test value. The results of the study based on the CVI average value assessment of expert validators and practitioner validators approached one with the very good category. The reliability of learning devices above 75% indicates that all aspects assessed are included in the reliable category. The results of the response of students obtained <80% with practical criteria and the average implementation of learning for three meetings was 87.7% with very practical criteria. The N-gain result of the concept mastery is 0.63 in the medium category. Based on these results, it can be concluded that guided inquiry learning tools to improve students' mastery of physics concepts are valid, practical, and effectively used in learning.